Effects of Gliding Properties of Cross-Country Skis on the Force Production During Skating Technique in Elite Cross-Country Skiers - Ohtonen, O.; Lindinger, S.; Linnamo, V. (International Journal of Sports Science and Coaching, 2013)
The aim of the present study was to examine how different gliding conditions of skis affect performance, cycle characteristics and leg and pole force production during V2 skating. Ten elite skiers skied on 100 m uphill (4°) at three different constant speeds (4.0, 4.8 and 5.6 m/s) and maximum speed using two differently prepared skating skis (fast and slow ski). With the slow ski, maximum speed was 6.4 % slower than with the fast ski. With constant speeds, cycle time got shorter due to a decrease in the recovery time of the leg and pole. Peak pole force and average cycle force increased as well as lateral leg forces while there were no changes in the vertical leg forces. A strategy for how skiers adapt on slower conditions was found. Skiers increased pole and lateral leg forces with slower speeds and with faster speeds, skiers increased the skiing frequency.